KEPEMIMPINAN TRANSAKSIONAL DAN DISIPLIN KERJA PT. MG SEMARANG - Ivana Indrianti Leksono; Sutarto Wijono (Program Studi S1 Psikologi, 2020)
This study aims to analyze the relationship between transactional leadership and work discipline at PT. MG Semarang. The subjects used in this study are employees who are still actively working at PT. MG Semarang. The population in the company is 100 employees and the sample to be used is 50 employees at PT. MG Semarang who had previously been willing to be a participant in this study. This subject was found from employees at PT. MG Semarang by taking data random sampling technique which is done by making a lottery with each name of the employee who came out who will get and fill out the questionnaire that has been provided in this study. The data scale collection method used by the author is by using the scale of transactional leadership by Robbins (2007) and work discipline by Rivai (2005). The data obtained were then performed statistical tests with correlation analysis with Spearman's rho between transactional leadership variables with work discipline. The results of the data obtained after statistical tests in this study are that there is no significant relationship between the variables of transactional leadership with work discipline, with an r value of 0.210; p> 0.05. The absence of a relationship between transactional leadership and work discipline can be interpreted, transactional leadership in PT. MG Semarang does not give a role in work discipline to its employees. Keywords: transactional leadership; work discipline